Economic growth and resources : proceedings of the fifth world congress of the International Economic Association held in Tokyo, Japan, 1977 - International Economic Association; Malinvaud, Edmond (New York : Macmillan Press, 1979)
This book is about remarkable growth of the industrialized market economies and the forces which account for the notable experiences
Volume 1: The major issues.
Includes bibliographical references and index.
oo 10/09/2018
Loans
Keywords: Economic development; Economic policy; Natural resources; Japan